Analysis of Contact Strength of Asymmetric Gear for Small Diameter Turbodrill Reducer - Zhang Xiang; Zhou Qin; Zhang Kai (Jixie chuandong)
Small diameter turbodrill with reducer is widely used in the field of geological drilling，but the radial size of the turbodrill is strictly limited and the reducer requires a high output torque，so it is of great engineering significance to optimize the structure of the asymmetric gear to improve its contact strength. Taking the sun gear and planet gear in the <alternatives>ϕ <?fx-imagestate width="2.37066674" height="3.38666677"?> <?fx-imagestate width="2.37066674" height="3.38666677"?> </alternatives>127 mm turbodrill reducer as study object，based on the Hertz contact theory，it is obtained that the pressure angle and curvature radius are important parameters affecting the contact stress of the asymmetric gear. In-depth study of the variation of contact stress of asymmetric gears under different pressure angles of the driving side. Combined with finite element analysis，the contact stress distribution of gear pair under different parameters is obtained，and the pressure angle of asymmetric gear is optimized. The results show that increasing the pressure angle of the driving side can increase the contact curvature radius and decrease the contact stress of the asymmetric gear. With the increase of pressure angle of the gear，the contact stress of the gear decreased by 23% and the output torque increased by 40%. Asymmetric gear of this type of reducer，its pressure angle of driving side should be selected in the range of 20° to 30°.